MSME Empowerment Assistance Program in Marikangen Village, Plumbon District, Cirebon Regency through Business Coaching and Appreciative Inquiry Activities - Bustaman; Muktar (PT FORMOSA CENDEKIA GLOBAL, 2022)
The MSME sector is a community-based business unit that is vulnerable to intense business and marketing competition. So, all efforts or investments to help MSMEs to improve their business capabilities are something worth fighting for. This community service process is carried out using an action research approach, with business coaching and appreciative inquiry techniques. Business coaching efforts are aimed at building business actors' awareness of the business they are doing, knowing more about their potential customers, and identifying key activities and partners, while appreciative inquiry is carried out to build discussions where participants can listen to each other's inspiration and experience building the best business from fellow business actors. . As a result, the participants know more about their business and are more enthusiastic about building networks among themselves.